ASSESSMENT OF THE IMPACT OF PHYSICOCHEMICAL QUALITIES OF SOILS IN GREYWATER USED FOR IRRIGATING LETTUCE PLANT (Latuca sativa) - M. Z. KARKARNA; RISIKAT ALABI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
The study aimed at assessing the effects of physicochemical properties of soils in greywater use for irrigation.Six weeks seeds of Lettuce (Latuca sativa) were sown in plastic flower pots containing loamy soil, plant monitoring routine was done weekly and data were anlayzed using excel while sampling of both water and soil were conducted before and after planting of which the samples were taken for analysis to the laboratory for physical and chemical parameters. The data obtained were analyzed using descriptive statistics.The pH, Ca, Mg, K, and Na levels in water and soil samples were all within WHO (1984) recommended ranges, indicating that greywater had no impact on soil quality. According to the report, research should be conducted on a regular basis to investigate the qualities of some physic-chemical properties and harmful compounds found in greywater irrigation and their impact on plant growth.